Hubungan Self Care Management Dengan Kadar Gula Darah Penderita Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Sawah Lebar Kota BengkuluTahun 2025 - Dennisa Novita Agustin; Emi Pebriani; Erlina Panca Putri (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Diabetes Mellitus is a chronic metabolic disease characterized by increased blood glucose levels due to impaired insulin secretion or insulin resistance. One of the factors that influence blood glucose control in patients with Diabetes Mellitus is self care management. Self care management is the ability of patients to perform self-care such as regulating diet, physical activity, medication adherence, monitoring blood glucose levels, and foot care. This study aims to determine the relationship between self care management and blood glucose levels in patients with Type 2 Diabetes Mellitus in the working area of Sawah Lebar Public Health Center, Bengkulu City. This study used a cross sectional research design. The sample in this study were patients with Type 2 Diabetes Mellitus who visited the Sawah Lebar Public Health Center using an accidental sampling technique. Data analysis was performed using univariate and bivariate analysis with statistical tests. The results showed that most respondents had good self care management and some respondents had controlled blood glucose levels. The results of bivariate analysis showed that there was a significant relationship between self care management and blood glucose levels in patients with Type 2 Diabetes Mellitus with a p-value < 0.05. The conclusion of this study is that there is a relationship between self care management and blood glucose levels in patients with Type 2 Diabetes Mellitus. Health workers are expected to increase education regarding self care management for patients with diabetes mellitus so that blood glucose levels can be well controlled.